Production, Optimization and Application of Bioemulsifier Extracted from Pseudomonas aeruginosa - Alaa Raheem Kazim; Hussam Mahmood Hassan; Suaad Ali Ahmed (World Journal of Experimental Biosciences, 2017)
Pseudomonas aeruginosa was isolated from soil and tested for bioemulsifier production when growing in mineral salt broth medium (production medium) that containing sunflower oil as carbon source. Several nutritional factors, environmental conditions, carbon, nitrogen sources, temperature, incubation period and pH were tested to evaluate the most favorable conditions for bioemulsifier production. The activity of bioemulsifier produced from P. aeruginosa as antibacterial substance was examined against many pathogenic bacteria. Maximum production of bioemulsifier was (100%) observed when P. aeruginosa grown in mineral salt broth medium with seasam oil and NH4Cl as carbon and nitrogen sources, incubated at 30 ºC for 3 days, pH 9. Bioemulsifier extracted from P. aeruginosa showed antibacterial activity by reducing growth of several pathogenic bacteria (Staphylococcus aureus, Bacillus subtilis, Proteus mirabilis and Escherichia coli.
Keywords: Bioemulsifier, Emulsification Index (E24%), Pseudomonas aeruginosa.